Disaster Management Literacy in Higher Education Environment: A Study of Students at Universitas Tidar - Atika, Atika; Suwandoko, Suwandoko; Ramadani, Shefa Dwijayanti; Prawenti, Herlita; Triastanti, Resti Kurnia; Mukti, Ari; Muqtada, Moh. Rikza (Sumatra Journal of Disaster, Geography and Geography Education, 2024)
This study aims to explore the level of understanding (literacy) of Universitas Tidar students regarding disaster management. This research uses survey research methods with a quantitative approach that processes and interprets data in the form of numbers and calculations. The population of this study is active students of Universitas Tidar with a total of 13,176 students. The research sample was 910 students from five faculties at Universitas Tidar, namely the Faculty of Economics, Faculty of Social and Political Sciences, Faculty of Teacher Training and Education, Faculty of Agriculture, and Faculty of Engineering. The determination of the research sample was carried out using the random sampling method. The results stated that the majority of students had a high level of disaster preparedness in the category of knowledge parameters about disasters and resource mobilization, while the parameters of disaster emergency response plans, disaster warning and disaster preparedness showed that the position of disaster management literacy was generally still in the medium category.